'Sancta Cæcilia Rediviva'. Elizabeth Linley: Repertoire, Reputation and the English Voice. (12th November 2015) - Aspden, Suzanne
Abstract: In the early 1770s, Elizabeth Linley was, for a few short years, not just Britain's most celebrated singer, but also the subject of almost cult-like devotion. Her brief career demonstrated a general awareness on the part of audience, singer and managers alike of the value of enmeshing of art, voice and life in the construction of a successful public persona. The extraordinary adulation she inspired suggests more than just canny use of publicity, however: her cultivation of an apparently distinctive sound and association with a particular repertoire – Handelian oratorio – at a time when Handel was particularly revered suggests British interest in the development of a national musical voice, as well as repertoire.